Relationship Between Personality Measures and Perceived Mental Fatigability. (August 2022) - Allen, Hannah L.; Gmelin, Theresa; Moored, Kyle D.; Boudreau, Robert M.; Smagula, Stephen F.; Cohen, Rebecca W.; Katz, Rain; Stone, Katie; Cauley, Jane A.; Glynn, Nancy W.; ,
Objective: Examine the association between personality measures and perceived mental fatigability. Methods: We performed a cross-sectional analysis in N =1670 men, age 84.3±4.1 years. Multivariable linear regression models were used to examine the covariate adjusted association between personality measures (conscientiousness, optimism, goal reengagement, and goal disengagement) and perceived mental fatigability (measured with the validated 10-item Pittsburgh Fatigability Scale, PFS). Results: One standard deviation lower conscientiousness (β=−0.91, p <.0001) and optimism (β=−0.63, p <.0001), and higher goal reengagement (β=0.51, p =.01) scores were independently associated with higher PFS Mental scores adjusted for age, cognitive function, self-reported health status, depressive symptoms, sleep disturbance, physical activity, and goal disengagement. Discussion: Lower conscientiousness, optimism, and higher goal reengagement were linked with more severe perceived mental fatigability in older men. Personality traits may potentially contribute to early risk assessment for fatigability in later life. Future work should be longitudinal in nature and include personality assessments to confirm the temporality of the relationships observed.